The Read Feed – Reviews. Issue 2 (3rd April 2017) - Boykin Nolen, Trina; Parang, Elizabeth
ABSTRACT: Trina Boykin Nolen reviews The Craft of Librarian Instruction: Using Acting Techniques to Create Your Teaching Presence;Elizabeth Parang reviews Encoding Space: Shaping Learning Environments That Unlock Human Potential .